177k views
2 votes
Find the equation of the following ellipse. Express your answer in standard form.Enable Zoom/PanPrev

Find the equation of the following ellipse. Express your answer in standard form.Enable-example-1

1 Answer

1 vote
Answer:
((x+3)^(2))/(4)=((y+1)^(2))/(16)

Explanations:

The equation of an ellipse is of the form:


((x-h)^2)/(a^2)=((y-k)^2)/(b^2)

The center of the ellipse, (h, k) = (-3, -1)

The horizontal radius, a = 2

The vertical radius, b = 4

Substitute these values into the equation


\begin{gathered} ((x-(-3))^2)/(2^2)=((y-(-1))^2)/(4^2) \\ \\ ((x+3)^2)/(4)=((y+1)^2)/(16) \end{gathered}

User Pfrenssen
by
4.7k points